As implicações psicossociais da pobreza na relação entre sentido de comunidade e desigualdades sociais de gênero no Parque da Liberdade - Barbosa, Vilkiane Natercia Malherme (2020)
In this work it is relevant to discuss the relationship between Sense of Community (CS), Multidimensional Poverty (PM) and Gender. For this, it is necessary to discuss what we understand about these categories and the possible relationships they can establish. We understand the complexity of establishing such a connection, but we believe that in everyday community life these are relevant for promoting strategies of psychosocial interventions as effects for facilitating processes of social change. In this way, Sense of Community can be understood as an expression of our others, connecting with an intersectional perspective that recognizes people's ways of life from their contexts, fostering strategies for strengthening individual and collective community identities. It is pointed out that the conception of Poverty defended here is multidimensional, based on the approaches of empowerment. And that the gender perspectives dealt with here aim to reveal the social and gender inequalities suffered by women from an intersectional perspective. The overall objective of the project is to analyse the impacts of poverty in the sense of the community of residents of the Redemptive Liberty Park/CE from a gender perspective. Specific objectives are: to describe the conditions of multidimensional poverty experienced in the community of Liberty Park; to understand the meanings of the sense of community developed by the population of Liberty Park; to compare the relationship between the sense of community and the dimensions of poverty; to analyse from an intersectional perspective the categories of sense of community and multidimensional poverty from the experience of women. The methodological proposal of this project is a mixed delineation. What is proposed, then, is the combination of quantitative and qualitative outlines in a mixed and intersectional perspective. In the first quantitative phase, we counted on a representative sample of the community of 128 people from a questionnaire, which counted on socio-demographic data, the IMPM and the IASC (in annex). Descriptive statistics, mean comparison, test t, ANOVA, Pearson's r correlation, multiple linear regression and moderation analysis were performed with the help of the SPSS program. The findings of this phase pointed to the relevance of understanding the CS related to the dimensions of poverty, from a multidimensional perspective. It was noted that the most significant dimensions in this relationship were the dimensions of psychological aspects of poverty and housing, and more robust analyses pointed out that the first of these dimensions has more lasting and expressive effects on the population under study. In the qualitative phase, ten women participated and a semi-structured interview was applied with them on the themes of the research. The analysis carried out was the categorical content analysis. The results pointed to the effects that the inequalities of gender possess on the SC, as the despontecialization of the active social participation of the women in the social fabric, as well as the relations that these inequalities have with the conditions of lived poverty, that become more oppressive the women. We defend this mixed approach as we consider the complex psychosocial, symbolic and subjective processes of social actors and actresses. The results of both studies demonstrate the complex relationships between SC, MP and Gender Social Inequalities that have psychosocial implications for the ways of life developed by people in this territory, especially women, revealing relationships of domination and oppression, but also possibilities of resistance. We believe that understanding this relationship within the community context can help to read the realities lived and facilitate the proposition of strategies for confronting poverty and strengthening sociocommunity relations.